GIS - Clokey, Joe; Clokey, Jora; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2005)
This program effectively shows what GIS is and what it can do. See how GIS can help in land use decision making, at a number of different levels. This tools allows us to overlay and process data that in important to our present and future decision making
Title from title screen
Host: Jim Harrigan
DVD format
Keywords: Geographic information systems